2015
DOI: 10.1002/jocb.134
|View full text |Cite
|
Sign up to set email alerts
|

Creative Expression and Its Evaluation on Work‐Related Verbal Tasks: A Comparison of Chinese and German Samples

Abstract: Two studies comparing Chinese and German samples by using work-related verbal creativity tasks examined the role of culture in creative expression thereby also exploring culture's potential influence on creativity judgements. In Study 1, German participants (N = 60) scored higher than Chinese respondents (N = 60) in a work-related unusual uses test on all objective creativity measures. Study 2 (Chinese: N = 59, German: N = 52) replicated these findings by applying an occupational creative problem-solving task … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 74 publications
(105 reference statements)
4
8
0
Order By: Relevance
“…The results of this study partially confirmed our second hypothesis and replicated the findings from past studies ( Niu et al, 2007 ; Lun et al, 2010 ; Wong and Niu, 2013 ; Tang et al, 2015 ). As predicted, there was a significant main effect for culture in students’ performance for all six measures in the two-C analysis model.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of this study partially confirmed our second hypothesis and replicated the findings from past studies ( Niu et al, 2007 ; Lun et al, 2010 ; Wong and Niu, 2013 ; Tang et al, 2015 ). As predicted, there was a significant main effect for culture in students’ performance for all six measures in the two-C analysis model.…”
Section: Discussionsupporting
confidence: 91%
“…Historically, creativity studies have suggested that individuals from non-Western cultures are not as creative as Westerners ( Torrance, 1974 ; Jellen and Urban, 1989 ; Niu and Sternberg, 2001 ; Tang et al, 2015 ). For example, in one study, Americans generated more aesthetically pleasing artworks (as judged by both American and Chinese judges) than Chinese ( Niu and Sternberg, 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…Because individual innovation shares similarities with strategic scanning ( e.g. identifying opportunities for change; Parker and Collins, ), we encourage future research to investigate whether our findings transfer to innovative and creative behaviour (Tang et al, ).…”
Section: Discussionmentioning
confidence: 95%
“…Collectivism, in contrast, prioritizes the group over the self and underlines collective interests, common values/goals, and interdependence of individuals ( Hofstede, 1980 ; Triandis, 1995 ). Individualism and collectivism are among the most frequently studied cultural dimensions in psychological and social sciences (see a review, Oyserman et al, 2002 ; Taras et al, 2010 ) and have been often applied to explain the differences between the East and the West in creativity studies as well (e.g., Niu and Sternberg, 2001 ; Yi et al, 2013 ; Tang et al, 2018 ).…”
Section: Theory and Hypothesesmentioning
confidence: 99%